The impact of the global financial turmoil and recession on Mediterranean countries' economies - Michael Sturm; Nicolas Sauter (European Central Bank (ECB), 2010)
This paper reviews the impact of the global financial turmoil and the subsequent recession on the economies of southern and eastern Mediterranean countries. The major effects on the economies of this region have come through transmission channels associated with the real economy, i.e. the global recession. These are, in particular, declines in exports, oil revenues, tourism receipts, remittances and foreign direct investment (FDI) inflows, with the drop in exports so far appearing to have had the strongest impact. As a result, real GDP growth has weakened in the wake of the global crisis. However, the weakening of economic activity in the Mediterranean region has been less pronounced than in advanced economies and most other emerging market regions. The main reason for this is that the direct impact of the global financial turmoil on banking sectors and financial markets in Mediterranean countries has been relatively limited. This is mainly due to (i) their lack of exposure to US mortgage-related assets that turned “toxic”, a feature the region shares with other emerging markets, and (ii) the limited financial development of many countries in the region and their limited integration into global financial markets, a feature that distinguishes the region from other emerging markets and, in particular, from the euro area's neighbours to the east. Notwithstanding the relative resilience of southern and eastern Mediterranean countries in the wake of the global crisis, the region faces significant challenges. In particular, many countries need significantly higher growth rates to address the employment challenge posed as a consequence of demographic developments.
Keywords: C43; C51; D91; 330; financial sector; Global economic crisis; International spillovers; Mediterranean countries; Wirtschaftskrise; Finanzkrise; International; Spillover-Effekt; Wirkungsanalyse; Mittelmeerraum